Students' Perceptions of Using TikTok in Learning English Vocabulary at Senior High School - Vianny Kurniawan; Paulina Novarita; Siti Sopiah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study investigates students' perceptions of using TikTok in learning English vocabulary at SMAN 1 Margaasih, Bandung. The increasing integration of social media in students' daily lives has made platforms like TikTok a potential medium for educational purposes, yet most existing studies on TikTok as a vocabulary learning tool have focused on university EFL learners or measured students' general attitudes without disaggregating perceptions into specific usefulness and ease-of-use dimensions, leaving senior high school students underrepresented in this line of research. This study addresses that gap through a descriptive quantitative approach using a 16-item Likert-scale questionnaire adapted from Alshreef and Khadawardi (2023), grounded in the Technology Acceptance Model (TAM) by Davis (1989) with two dimensions: Perceived Usefulness (PU) and Perceived Ease of Use (PEOU). Data were collected from 32 eleventh-grade students selected through purposive sampling, and the instrument was confirmed valid and reliable through Pearson product-moment correlation and Cronbach's Alpha testing. The results showed that students hold a positive perception of TikTok in both dimensions, with the PU dimension yielding a mean score of 3.91 (Positive) and the PEOU dimension yielding a mean score of 4.00 (Positive), producing an overall mean of 3.95 (Positive). Item 2 recorded the highest score in the PU dimension (mean = 4.16), indicating that TikTok is particularly helpful in understanding new vocabulary meanings, while Item 10 reached the Very Positive category in the PEOU dimension (mean = 4.22), reflecting students' strong agreement that TikTok is easy to access for vocabulary learning. These findings extend TAM-based evidence, previously drawn mainly from university samples, to the senior high school context, supporting the model's applicability across educational levels of language learning. The results suggest that TikTok can be integrated purposefully into secondary English vocabulary instruction as a supplementary medium to strengthen students' engagement with new words beyond the classroom.